Nucleotide binding to the homodimeric MJ0796 protein: a computational study of a prokaryotic ABC transporter NBD dimer. - Campbell, J; Sansom, MS (2005)
Transport by ABC proteins requires a cycle of ATP-driven conformational changes of the nucleotide binding domains (NBDs). We compare three molecular dynamics simulations of dimeric MJ0796: with ATP was present at both NBDs; with ATP at one NBD but ADP at the other; and without any bound ATP. In the simulation with ATP present at both NBDs, the dimeric protein interacts with the nucleotides in a symmetrical manner. However, if ADP is present at one binding site then both NBD-NBD and protein-ATP interactions are enhanced at the opposite site.